PERIPHERAL NERVE HYPER- EXCITABILITY - Waseem Wali Muhammad (Army Medical College Rawalpindi, 2019)
We report a case of a 32 year old patient of peripheral nerve hyper excitability who presented with fasciculation in all four limbs, muscle aches and fatigue. Electromyography study showed spontaneous, continuous activity in the form of discharges with high frequency. His symptoms disappeared when plasma exchange was employed along with steroid administration.